Integrating Neem’s Medicinal Properties into Microbiology Education A Systematic Review - Muhammad Anees; Anna Rakhmawati; Kartika Ratna Pertiwi; Sajid Iqbal (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2025)
This systematic review investigates the integration of Azadirachta indica (Neem) as potential learning resources into Microbiology topics in Biology learning, focusing on its bioactive compounds and medicinal properties such as antimicrobial agent. Neem’s bioactive compounds, such as azadirachtin, nimbolide, and gedunin, exhibit potent antimicrobial activity against a broad spectrum of pathogens, including E. coli, S. aureus, and Candida albicans. These properties make Neem a compelling natural alternative in the fight against antimicrobial resistance (AMR), a growing global health concern. Drawing on 20 studies published between 2014 and 2024, this review highlights Neem’s values in microbiology curricula by offering students hands-on opportunities to study natural antimicrobial agents while fostering critical thinking and practical skills in microbiology. Additionally, incorporating Neem into education promotes environmental sustainability whilst acts as an appreciation for traditional local wisdom